First, add #color(red)(4x^2)# to each side of the equation to put the equation into standard quadratic form while keeping the equation balanced:
#color(red)(4x^2) + 7x + 1 = color(red)(4x^2) - 4x^2#
#4x^2 + 7x + 1 = 0#
We can now use the quadratic equation to solve this problem:
The quadratic formula states:
For #color(red)(a)x^2 + color(blue)(b)x + color(green)(c) = 0#, the values of #x# which are the solutions to the equation are given by:
#x = (-color(blue)(b) +- sqrt(color(blue)(b)^2 - (4color(red)(a)color(green)(c))))/(2 * color(red)(a))#
Substituting:
#color(red)(4)# for #color(red)(a)#
#color(blue)(7)# for #color(blue)(b)#
#color(green)(1)# for #color(green)(c)# gives:
#x = (-color(blue)(7) +- sqrt(color(blue)(7)^2 - (4 * color(red)(4) * color(green)(1))))/(2 * color(red)(4))#
#x = (-color(blue)(7) +- sqrt(49 - 16))/8#
#x = (-color(blue)(7) +- sqrt(33))/8#